Towards an Open Repository for Teaching Software Modeling applying Active Learning Strategies - Silva, Williamson; Gadelha, Bruno; Steinmacher, Igor; Conte, Tayana (Proceedings of the ACM/IEEE 42nd International Conference on Software Engineering: Software Engineering Education and Training, 2020)
Modeling is a core topic in Software Engineering Education. Nevertheless, students face difficulties while learning software modeling. To teach software modeling effectively in computing courses, instructors who usually employed traditional methods could use active learning strategies. However, instructors are reluctant to change their teaching approaches due to several barriers that hinder the application of active learning strategies. Besides, relatively little research addresses how to mitigate them. The objective of this research is to help instructors implementing active learning strategies when teaching software modeling with UML diagrams. To achieve this objective, we conducted a Design Science Research (DSR). We proposed an artifact called OpenSMALS, an Open Repository for teaching Software Modeling applying Active Learning Strategies. OpenSMALS provides specific guidelines on how instructors can apply these strategies and helping instructors to identify the active learning strategies best suit their teaching context. We performed four DSR Design Cycles-in four different universities-to evaluate and evolve OpenSMALS. Our results show that OpenSMALS satisfactorily reduced the barriers faced by instructors, and it achieved an appropriate maturity level to be adopted by other instructors.